Pharmacodynamics of nine generic products of amikacin compared with the innovator in the neutropenic mouse thigh infection model (2015)
ABSTRACT: Background Previously, we validated the mouse thigh infection model to test the therapeutic equivalence of generic antibiotic products. Here, our aim was to compare the in vivo efficacy of amikacin products in clinical use in Colombia using this animal model. Results All except one generic product had the same in vitro potency, judging by the lack of differences on MIC and MBC compared with the innovator. However, eight of nine generic products failed in the neutropenic mouse thigh infection model to achieve the innovator’s maximum effect (E max ≤ 5.65 for the generics vs. 6.58 log10 CFU/g for the innovator) against Escherichia coli SIG-1, after subcutaneous treatment every 6 h with doses ranging from 1.5 to 3072 mg/kg per day. Conclusion As we demonstrated previously with other antibiotics such as vancomycin, gentamicin and oxacillin, the generic products of amikacin failed the in vivo efficacy testing. The therapeutic equivalence should be assessed in vivo before clinical approval of generic products.